Treatment of right ventricular outflow tract dysfunction: a multimodality approach. (29th April 2016) - Pluchinotta, Francesca Romana; Bussadori, Claudio; Butera, Gianfranco; Piazza, Luciane; Chessa, Massimo; Saracino, Antonio; Fernandez Sarabia, Javier; Giugno, Luca; Arcidiacono, Carmelo; Micheletti, Angelo; Negura, Diana Gabriela; Fesslova, Vlasta; et al.
Abstract: The right timing to replace the pulmonary valve in a patient with dysfunction of the right ventricular outflow tract is unknown. Both percutaneous pulmonary valve and surgical prosthesis are suitable options. In every patient, the right ventricle (RV) remodels and recovers differently after pulmonary replacement. Therefore, it is difficult to identify the best treatment option and to predict the long-term results. In the last few years, we focused our research on optimizing the characterization of these patients through advanced cardiovascular imaging in order to find possible variables, parameters, and reproducible measurements that can help us in the decision-making process. The aim of the present article is to present our ongoing research lines that focus on the characterization and optimal treatment approach to the dysfunction of the RVOT.